2021
DOI: 10.1186/s12862-021-01768-y
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of multiple chromosomal rearrangements in the genome of Willisornis vidua using BAC-FISH and chromosome painting on a supposed conserved karyotype

Abstract: Background Thamnophilidae birds are the result of a monophyletic radiation of insectivorous Passeriformes. They are a diverse group of 225 species and 45 genera and occur in lowlands and lower montane forests of Neotropics. Despite the large degree of diversity seen in this family, just four species of Thamnophilidae have been karyotyped with a diploid number ranging from 76 to 82 chromosomes. The karyotypic relationships within and between Thamnophilidae and another Passeriformes therefore rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 63 publications
2
10
0
Order By: Relevance
“…Although this diploid number is slightly lower than the "typical" avian karyotype (2n ≈ 80), we detected fissions of chromosomes homologous to ancestral pairs 5 and 6 (NGA5 and NGA6). Chromosome fissions involving the homologous chromosome to NGA5 are frequent in birds and have been reported in species from the following Neoaves orders: Accipitriformes, Charadriiformes, Eurypygiformes, Falconiformes, Gruiformes, Passeriformes, Trogoniformes, Piciformes, and Strigiformes [7,30,[42][43][44][45][46], while fissions in GGA6 have been detected previously only in Psittaciformes species [28,47,48] and in Crotophaga ani, a Cuculiformes species [27]. In addition, four chromosomal associations were detected in P. brasilianus, including associations between macrochromosomes (NGA5/7), macrochromosomes and microchromosomes (NGA8/12 and NGA9/10) and between microchromosomes (NGA11/13).…”
Section: Karyotype Of P Brasilianus (Suliformes)mentioning
confidence: 99%
See 1 more Smart Citation
“…Although this diploid number is slightly lower than the "typical" avian karyotype (2n ≈ 80), we detected fissions of chromosomes homologous to ancestral pairs 5 and 6 (NGA5 and NGA6). Chromosome fissions involving the homologous chromosome to NGA5 are frequent in birds and have been reported in species from the following Neoaves orders: Accipitriformes, Charadriiformes, Eurypygiformes, Falconiformes, Gruiformes, Passeriformes, Trogoniformes, Piciformes, and Strigiformes [7,30,[42][43][44][45][46], while fissions in GGA6 have been detected previously only in Psittaciformes species [28,47,48] and in Crotophaga ani, a Cuculiformes species [27]. In addition, four chromosomal associations were detected in P. brasilianus, including associations between macrochromosomes (NGA5/7), macrochromosomes and microchromosomes (NGA8/12 and NGA9/10) and between microchromosomes (NGA11/13).…”
Section: Karyotype Of P Brasilianus (Suliformes)mentioning
confidence: 99%
“…Recently, bacterial artificial chromosome (BAC) probes from the genomic libraries of chicken and zebra finch (Taeniopygia guttata, Passeriformes, Neoaves) have been applied successfully across multiple avian species totaling chromosome maps for 36 species from 12 different orders [15,16,[24][25][26][27][28][29][30]. Results from these studies suggested evolutionary stability in avian microchromosome organization, except in Falconiformes, Psittaciformes, and Cuculiformes species, in which microchromosomal fusions were found [15,16,24,25,27,28], demonstrating the usefulness of microchromosome BAC probes to provide a more extensive analysis of chromosomal evolution in birds.…”
Section: Introductionmentioning
confidence: 99%
“…Probes from the stone curlew ( Burhinus oedicnemus , BOE, 2n = 42, Charadriiformes) were the first set of chromosome-specific painting probes from Neoaves species that were able to cover the entire genome of a given bird species [ 24 ]. Thus, BOE painting probes have been used to establish genome-wide chromosomal homology among the karyotypes of eleven avian species in eight different orders [ 24 28 ]. The results demonstrate that BOE painting probes are robust tools for delineating avian chromosome evolution, especially for revealing the rearrangements that involve microchromosomes.…”
Section: Introductionmentioning
confidence: 99%
“…Because of technical limitations, however, most of the molecular cytogenetics studies in Passeriformes have focused only on the comparison of homology with chicken macrochromosomes [11]. For instance, up to now, only four Passeriformes species had their karyotype analyzed in detail, i.e., macro and microchromosomes: Taeniopygia guttata, Turdus merula, and Serinus canaria [17,21,22] from oscines suborder, and Willisornis vidua from suboscines suborder [23]. The results revealed that the microchromosomes were not involved in interchromosomal events in the oscines species.…”
Section: Introductionmentioning
confidence: 99%